The Alzheimer's disease sequencing project–follow up study (ADSP‐FUS): Increasing ethnic diversity in Alzheimer's genetics research with addition of potential new cohorts: Genetics/genetic factors of non‐Alzheimer's tauopathies. (7th December 2020) - Mena, Pedro Ramon; Kunkle, Brian W.; Faber, Kelley; Celis, Katrina; Adams, Larry D.; Foroud, Tatiana M.; Reyes‐Dumeyer, Dolly; Kuzma, Amanda B.; Naj, Adam C.; Martin, Eden R; Dalgard, Clifton; Schellenberg, Gerard D.; et al.
Abstract: Background: The ADSP‐FUS is a National Institute on Aging (NIA) initiative focused on identifying genetic risk and protective variants for late‐onset Alzheimer Disease (LOAD). A major concern in AD genetic studies is a lack of racial‐ethnic diversity. The ADSP‐FUS collects and sequences existing both ethnically diverse and unique cohorts with extensive clinical data to expand the utility of new discoveries for individuals from all populations. Additional multi‐ethnic cohorts are presently being recruited (e.g. Amerindian, Korean and Indian). Method: The cohorts consist of participants from studies of AD, dementia, and aging‐related conditions. Clinical classification (i.e., AD, dementia, and non‐affected) is implemented using algorithms based on a minimal set of criteria derived from standard measures (e.g., global cognitive screeners, dementia rating scales, etc.) and pertinent clinical history. Data dictionaries are generated for each cohort by clinical staff at Columbia University and University of Miami (UM). In total, ADSP‐FUS intends to sequence over 40, 000 individuals. Existing biospecimens were obtained and processed through the National Centralized Repository for Alzheimer's (NCRAD), the primary site for preparation and allocation of DNA, which is then delivered to the Uniformed Services University of the Health Sciences (USUHS) for whole genome sequencing (WGS). The resulting raw sequence data is delivered to the Genome Center for Alzheimer's Disease (GCAD) for processing and harmonization followed by quality control analysis at University of Pennsylvania and University of Miami into analysis‐ready genotype data. The final step is delivery of clinical, genotype and sequence data to the NIA Genetics of Alzheimer Disease Data Storage Site (NIAGADS), which serves as the ASDP‐FUS data storage, management and sharing center. Results: Over 30, 000 samples have been ascertained and are distributed as follows: 7, 896 with African ancestry; 9, 475 with Hispanic ancestry; 13, 531 with non‐Hispanic white ancestry (1, 400 EOAD and 3, 745 autopsy) and 89 with Amerindian ancestry. Conclusion: The ADSP‐FUS is designed to enhance ongoing efforts for the identification of shared and novel genetic risk factors for LOAD among different populations. This project will expand our current knowledge of potential genetic risk and protective variants for LOAD across all populations with the hope of developing new treatments.